Os valores religiosos e seus desdobramentos no cotidiano dos jovens - Vidal, Elisa Silva (2016)
The conservatism manifests itself in a timely manner in the brazilian contemporaneity and ideologically marks the discourse, actions and values perpetuated by religious institutions. Therefore, this research, based on the Marx’s social theory, aims to bring elements to analyze the representativeness of the conservative values in the everyday life of young people bound to different religions. For this purpose, we made a bibliographic research and subsequently a field research, where we applied semi-structured interviews with four youth – two evangelicals, one catholic and one umbandista – which considerer the religion as part of their life. This is therefore a modern theme, important for the apprehension of the young’s reality who adhere to the religions of the Brazilian conjuncture, aiming to contribute for the understanding of the values, expectations and life references of a population which is part of the professional activity of Social Service. In this perspective, this paper is of big relevance because it approaches a rarely considered subject on Social Sciences and it brings to the academy questions that help the understanding of the relation between conservatism, youth and religion